Feasibility of direct digital fabric printing on barong fabrics - Naval, Jamie Lyn Dagohoy
The Philippine textile industry, in pursuit of saving and strengthening itself, is looking for ways to develop and further advance the local production of textiles, especially, that of the Philippine tropical fabrics (Mauricio, 2013). As a way to contribute to the industry's revival and revitalization, specifically by looking into the development of and new solutions relating to Philippine tropical fabrics' design adaptability to commercial production, the study examined the technical feasibility and commercial viability of direct digital printing (DDP) on Barong fabrics. The fabrics were technically feasible in terms of their respective colorfastness to laundering and light. However, colorfastness to rubbing yielded noticeable staining and failed to pass both EU and US standard minimum requirements, and thus was not feasible on this aspect. It is recommended that further studies be made to assess the effect of direct digital fabric printing on the fabrics' physical properties. The fabrics were tested for commercially viability through a survey which indicated the fabrics to be innovative, vibrant and marketable. Potential target markets are designers and business owners. Current cost of the fabrics was found to be high. But in comparison to similar commercial fabrics, the cost fits rightly to prices of printed silk organza and organdi. Survey respondents recommended direct digital fabric printing on Philippine tropical fabrics, accessories and interior design as direct applications of the fabrics. DDP Barong fabrics can be used in the design and production of traditional and commercial garments. Digital fabric printing as a means of surface design treatment is recommended to develop various designs of Barong fabrics. Further studies on how to take care of, market and design fabrics are recommended to improve the direct digital printed Barong fabrics.